FUNGSIONALISASI HUKUM PIDANA TERHADAP PERTANGGUNGJAWABAN KORPORASI DALAM TINDAK PIDANA DIBIDANG ASURANSI - Rise Karmilia (Jurnal Ilmiah Cano Ekonomos, 2017)
The business world is increasingly complex in line with the awareness of the importance of legal protection and the security of property that makes the responsibility of individuals or legal entities increasing. Such security may take the form of legal documents, in the form of business agreements up to the document of insurance agreement that will not be separated from the possibility of a crime. Background by the complexity of problems in insurance crime, ranging from the use of smooth modus operandi, investigation, verification, to the problem of the lack of public knowledge about insurance. This research uses normative juridical method. Problems in the research is how the arrangement of criminal acts in the field of insurance in the positive law of Indonesia, how corporate responsibility in insurance crime and what factors are obstacles in the handling of criminal acts in the field of insurance as well as any efforts that can be done as a solution in mengfungsikan criminal law.